George Floyd's death and COVID‐19: inflection points in the Anthropocene Era?. Issue 3 (7th July 2021) - Merritt, Dennis
Abstract: George Floyd's death, the COVID‐19 pandemic and climate change are on a continuum from the immediate shock of viewing a video‐recorded murder, to millions dying worldwide from disease, to deaths related to climate change accumulating over a millennium. They participate in the powerful archetypes of death and inequality. 'Increase', Hexagram 42 in the I Ching, archetypically addresses inequalities at all levels – racial, economic, political and the profound imbalance between humans and the environment. Floyd's death highlights the consequences of systemic racism and income inequalities. The pandemic as 'nature's revenge' hits minority populations harder due to underlying health conditions resulting from poverty and greater exposure to the virus in the workplace. President Trump as Trickster showed Americans their shadow and his response to the pandemic amplified its severity. The pandemic has shocked our social, political and economic systems and paused our species rush into environmental disasters at many levels. The disruptions present opportunities for reflection, experimentation and developing new systems as old forms are challenged. The ecological dimensions of Jung's concepts emphasize interconnectedness at all levels and the paradigm shift he called a 'new age' provides a framework for altering the course of the Anthropocene Era. Abstract : La mort de George Floyd, la pandémie de COVID‐19 et le changement climatique sont sur un continuum: du choc immédiat à la vue d'un meurtre enregistré sur une vidéo, aux millions de personnes dans le monde mourant de maladie, aux morts en lien avec les changements climatiques qui s'accumulent depuis plus de mille ans. Tout cela participe aux archétypes puissants de la mort et de l'inégalité. 'L'augmentation', l'Hexagramme 42 du Yi King, aborde de manière archétypale les inégalités à tous les niveaux – racial, économique, politique et le déséquilibre profond entre les humains et l'environnement. La mort de Floyd souligne les conséquences du racisme systémique et des inégalités de revenus. La pandémie en tant que 'revanche de la nature' frappe les minorités plus durement du fait de conditions de santé fragilisées par la pauvreté et l'exposition plus élevée au virus sur le lieu de travail. Le président Trump comme archétype du filou a montré leur ombre aux Américains, et sa réponse à la pandémie en a amplifié la sévérité. La pandémie a secoué nos systèmes sociaux, politiques et économiques et provoqué une pause dans la précipitation de notre espèce vers des désastres environnementaux à plusieurs niveaux. Les perturbations offrent des opportunités pour réfléchir, pour expérimenter et développer de nouveaux systèmes tandis que les vieilles formes sont mises en cause. Les dimensions écologiques des concepts de Jung mettent l'accent sur l'aspect interconnecté à tous niveaux et le changement de paradigme qu'il a appelé « nouvel âge » fournit un cadre de travail pour modifier le cours de l'Ere de l'Anthropocène. Abstract : Der Tod von George Floyd, die COVID‐19‐Pandemie und der Klimawandel bilden ein Kontinuum von unmittelbaren Schocks: einen auf Video aufgezeichneten Mord zu sehen, über Millionen, die weltweit an Krankheit sterben, bis hin zu Todesfällen im Zusammenhang mit dem Klimawandel, der sich über ein Jahrtausend angesammelt hat. Sie nehmen an den mächtigen Archetypen von Tod und Ungleichheit teil. 'Mehren', Hexagramm 42 im I Ging, befaßt sich archetypisch mit Ungleichheiten auf allen Ebenen – rassisch, wirtschaftlich, politisch und dem tiefgreifenden Ungleichgewicht zwischen Mensch und Umwelt. Floyds Tod zeigt die Folgen von systemischem Rassismus und Einkommensungleichheiten auf. Die Pandemie als 'Rache der Natur' trifft Minderheiten aufgrund der zugrundeliegenden Gesundheitsbedingungen, die sich aus Armut und einer stärkeren Exposition gegenüber dem Virus am Arbeitsplatz ergeben, härter. Präsident Trump als Trickster zeigte den Amerikanern ihren Schatten und seine Reaktion auf die Pandemie verstärkte deren Schwere. Die Pandemie hat unsere sozialen, politischen und wirtschaftlichen Systeme erschüttert und den Sturmlauf unserer Spezies hinein in Umweltkatastrophen auf vielen Ebenen ausgesetzt. Die Zerrüttungen bieten Möglichkeiten zum Nachdenken, Experimentieren und Entwickeln neuer Systeme, da alte Formen in Frage gestellt werden. Die ökologischen Dimensionen von Jungs Konzepten betonen die Verbundenheit auf allen Ebenen und der Paradigmenwechsel, den er als 'neues Zeitalter' bezeichnete, bietet einen Rahmen für die Veränderung des Verlaufs des Anthropozäns. Abstract : La morte di George Floyd, la pandemia da COVID‐19 ed il cambiamento climatico sono su un continuum dallo shock immediato della visione dei video dell'uccisione, ai milioni di morti in tutto il mondo per la malattia, alle morti legate al cambiamento climatico accumulatosi nel millennio. Tutto questo partecipa al potente archetipo della morte e dell'ineguaglianza. 'Aumento', l'Esagramma 42 de I Ching, archetipicamente si riferisce alle ineguaglianze a tutti i livelli – razziale, economico, politico ed il profondo sbilanciamento tra esseri umani ed ambiente. La morte di Floyd mette in luce le conseguenze di un sistema razzista e delle conseguenti ineguaglianze. La pandemia come "la vendetta della natura" colpisce le minoranze più fortemente a causa delle condizioni di salute che derivano dalla povertà e dalla maggiore esposizione al virus nei luoghi di lavoro. Il Presidente Trump come Trickster ha mostrato agli americani la loro ombra e la sua risposta alla pandemia ne ha amplificato la gravità. La pandemia ha scioccato i nostri sistemi sociali, politici ed economici ed ha rallentato la nostra specie nella corsa verso il disastro ambientale a molti livelli. La distruzione presenta delle opportunità per una riflessione, per fare esperienza e per sviluppare nuovi sistemi laddove i vecchi sono messi in crisi. La portata ecologica dei concetti di Jung che enfatizzano l'interconnessione a tutti i livelli ed il cambio di paradigma che lui chiamava la "nuova era" offre una cornice per cambiare il corso dell'Era dell'Antropocene. Abstract : Смерть Джорджа Флойда, ковид‐19 пандемия и изменение климата находятся на континууме: непосредственный шок при просмотре видео записи убийства, миллионы умирающих во всем мире от болезни и накопившиеся за тысячелетие смерти, связанные с изменением климата. Все они отражают могущественные архетипы смерти и неравенства. «Приумножение», гексаграмма 42 в книге И Цзин, архетипически адресована неравенствам на всех уровнях – расовом, экономическом, политическом, а также сильному дисбалансу между человеком и окружающей средой. Смерть Флойда высвечивает последствия системного расизма и неравенства доходов. Пандемия как «реванш природы» ударяет сильнее по меньшинствам, так как из‐за бедности они живут в плохих для здоровья условиях и больше подвержены риску заражения на рабочих местах. Президент Трамп как Трикстер показал американцам их тень, а его реакция на пандемию только усилила проблемы. Пандемия потрясла наши социальные, политические и экономические системы, остановила наш бег как биологического вида к экологической катастрофе на многих уровнях. Возникшие сбои дают возможность для рефлексии, экспериментов и разработки новых систем, так как старым системам брошен вызов. Экологические аспекты концепций Юнга подчеркивают взаимосвязь на всех уровнях, а смена парадигмы, которую он назвал «новой эрой», формирует основу для изменения курса эпохи антропоцена. Abstract : La muerte de George Floyd, la pandemia del COVID‐19 y el cambio climático están en un continuum que va desde el shock de mirar una muerte a través de una cámara de video, a millones muriendo alrededor del mundo por una enfermedad, a muertes relacionadas con el cambio climático acumulándose a través de los milenios. Estos forman parte de los poderosos arquetipos de la muerte y de la desigualdad. "El Aumento", Hexagrama 42 en el I Ching, aborda arquetípicamente las desigualdades a todos los niveles – racial, económico, político y el desbalance profundo entre los humanos y el contexto. La muerte de Floyd evidencia las consecuencias de un racismo sistemático, y de las desigualdades en los ingresos. La pandemia, como 'venganza de la naturaleza' afecta más duramente a las poblaciones minoritarias debido a las condiciones básicas de salud resultantes de la pobreza y de una mayor exposición al virus en los lugares de trabajo. El presidente Trump como Trickster mostró su sombra a los americanos y su respuesta a la pandemia amplificó la severidad de esta. La pandemia ha impactado nuestros sistemas social, político y económico y detuvo, a muchos niveles, la carrera de nuestra especie hacia los desastres medioambientales. Las alteraciones presentan oportunidades para la reflexión, la experimentación y el desarrollo de nuevos sistemas a medida que son desafiadas las viejas formas. Las dimensiones ecológicas de los conceptos de Jung enfatizan la interconectividad a todos los niveles y el cambio de paradigma que denominó'nueva era' provee un marco de referencia para alterar el curso de la Era Antropoceno. Abstract : George Floyd的死亡和COVID‐19:人类世时代的拐点? George Floyd的死亡, 新冠疫情及气候变化, 处于同一个系列中, 从看到视频记录的谋杀所受到的即刻惊吓, 到全球上百万因病而死去的人, 再到千年间与气候变化相关所积累的死亡。他们参与了死亡与不公平的强大原型。易经第42卦"益", 原型性地叙述了各种层面的不公平性——种族, 经济, 政治, 以及人类与环境间深远的失衡。Floyd的死亡凸显了体系中的种族主义和收入不公平的后果。疫情作为"自然的报复"对少数人群的挫伤更加严重, 因为其基础的健康条件不良, 而这来源于其贫穷和工作环境中更多暴露在病毒之下。特朗普总统作为愚人者, 向美国人展现了他们的阴影, 而他对于疫情的反应加重了它的严重性。疫情震惊了我们的社会、政治和经济体系, 在诸多领域暂停了我们这个物种冲向环境的灾难。这一中断为我们提供了机会去反思, 在旧的形式受到挑战的时候, 去试验和发展新的体系。荣格概念中的生态学角度强调各个层面的互联性, 而他所称的"新时代"的范式为人类世时代进程的转变提供了一个架构。